2019
DOI: 10.1094/pdis-08-18-1375-re
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Dispersal and Glomerella Leaf Spot Progress Within Apple Canopy in Brazil

Abstract: Glomerella leaf spot (GLS) of apple is caused by three different Colletotrichum species complexes. This study evaluated the dispersal of Colletotrichum spores related to GLS temporal progress and defoliation. Spores were monitored by air and water runoff in different plant heights, and the temporal progress of GLS and defoliation were assessed. Spores of the pathogen were first cached in the lower part of the tree closer to the ground, confirming the importance of dead leaves on the ground as main source of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Ratio scales Many diseases lend themselves to severity estimation by ratio scales. The percentage scale is a widely applied scale to visually estimate severity (recent examples include Gent et al 2018;Bock and Chiang 2019;Hamada et al 2019;Xu et al 2019). The percentage scale ranges from zero to 100% and a rater gauges the proportion of the organ showing symptoms and estimates the severity accordingly.…”
Section: Methods Of Visual Estimation and Nature Of The Datamentioning
confidence: 99%
“…Ratio scales Many diseases lend themselves to severity estimation by ratio scales. The percentage scale is a widely applied scale to visually estimate severity (recent examples include Gent et al 2018;Bock and Chiang 2019;Hamada et al 2019;Xu et al 2019). The percentage scale ranges from zero to 100% and a rater gauges the proportion of the organ showing symptoms and estimates the severity accordingly.…”
Section: Methods Of Visual Estimation and Nature Of The Datamentioning
confidence: 99%
“…Rajasab and Chawda [62] demonstrated that single drops (a drop was 3 mm in diameter and carried till 2000 conidia) were able to wash conidia from acervuli of C. gloeosporioides onto onion leaves. The washing-off of Colletotrichum conidia within an apple tree canopy was also demonstrated by Hamada et al [64], and Guyot et al [65] found that a light rain (a "drizzle") can disperse Colletotrichum conidia within rubber trees. Daykin and Milholland [18] reported that the numerous insects attracted to rotting fruits may spread the secondary inoculum of C. gloeosporioides.…”
Section: Discussionmentioning
confidence: 56%
“…Pathogenic fungi are involved in several crop diseases and cause enormous economic loss each year. The GLS pathogen mainly damages apple leaves causing dark spots followed by their dryness resulting in severe defoliation within 5-7 days of development ( Hamada et al, 2019 ; Sutton and Sanhueza, 1998 ; Wang et al, 2012 ). In apple leaves and fruits, C. gloeosporioides causes slightly small lesions, which develop into bitter rot ( Velho et al, 2015 ).…”
mentioning
confidence: 99%